2014
DOI: 10.3390/rs61111031
|View full text |Cite
|
Sign up to set email alerts
|

Surface Daytime Net Radiation Estimation Using Artificial Neural Networks

Abstract: Net all-wave surface radiation (Rn) is one of the most important fundamental parameters in various applications. However, conventional Rn measurements are difficult to collect because of the high cost and ongoing maintenance of recording instruments. Therefore, various empirical Rn estimation models have been developed. This study presents the results of two artificial neural network (ANN) models (general regression neural networks (GRNN) and Neuroet) to estimate Rn globally from multi-source data, including r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 44 publications
(51 reference statements)
0
21
0
Order By: Relevance
“…Remote sensing retrieval has become one of the most important methods for obtaining the radiation data [4]. However, clouds make it impossible to retrieve surface thermal radiation components directly from satellite observations, and the alternative solution is to estimate the all-wave net radiation from the satellite shortwave net radiation product, in conjunction with other information [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing retrieval has become one of the most important methods for obtaining the radiation data [4]. However, clouds make it impossible to retrieve surface thermal radiation components directly from satellite observations, and the alternative solution is to estimate the all-wave net radiation from the satellite shortwave net radiation product, in conjunction with other information [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The variables considered in this study are shown in Table 2. The readers are referred to Jiang et al [37] for more information about these data. R si * stands for the GLASS R si product and was used for global GLASS daytime R n production in this study.…”
Section: Datamentioning
confidence: 99%
“…Jiang et al [37] applied the GRNN model for daytime R n estimation, and the evaluation results proved that this model worked very well and was stable under various conditions. The architecture of the GRNN model used in this study is shown in Figure A1.…”
Section: B General Regression Neural Network (Grnn) Modelmentioning
confidence: 99%
See 2 more Smart Citations